( x - 5) / ( -6 - 5) = (y - 4)/( 3 - 4) <=> (x-5)/(-11) = (y-4)/(-1) <=> x - 5 = 11y - 44 <=> x - 11y + 39 = 0;

First you have to find the slope of the line. (y2 -y1) / (x2 - x1) = slope so (3 - 4) / ( -6 - 5) = -1/ -11 so the slope of the line is 1/11 Now you write y = mx + b then substitute in one of the points with x and y 4 = (1/11)(5) + b 4 = 5/11 + b -5/11= - 5/11 change the 4 into 44/ 11 and subtract 44 / 11 - 5/11= b 39/11 = b now it depends on your teacher and text usually, you can substitute the fraction for your b y = mx + b y = 1/11 x + 39/11 so this is your answer Does that make sense or did I make a mathematical error?